Chapter 1 Intersections of Modalities from Medieval to Modern Times - Włodarczyk, Matylda (Taylor & Francis, 2023)
This paper argues that the integration of the multimodal and the multilingual which pre-exists modern digital media is all but haphazard. Thus their dynamics and trends that have endured and developed over the centuries call for a systematic scholarly exploration. For instance, in historical texts and contemporary social media alike preattentive engagement techniques are implemented by content producers in order to guide processing. Other manifestations of the multimodal and multilingual interplay involve orthographic aesthetics which encodes social evaluations and commentary of (linguistic) otherness in the late modernity, while visual diamorphs, brevigraphs and non-alphabetic symbols embody the prestige of medieval de luxe manuscripts. Bilingualism in contemporary social media is as purposeful and commercially devised a tool as the graphics and photos placed in blogs and vlogs by microinfluencers. The paper offers an approach that paves the way for generalisations and extension to cover further data representing other languages and periods.